Analisis Break Even Point sebagai Dasar Evaluasi Profitabilitas pada Pekerjaan Struktur Beton (Studi Kasus Pembangunan Pandawa Residence) - Made Sudiarsa; I Nengah Darma Susila; Wayan Darya Suparta; Made Budiadi (Politeknik Negeri Lhokseumawe, 2026)
Technological aspects play a crucial role in construction projects, particularly in selecting concrete work implementation methods. The Pandawa Residence project applies two methods for concrete structural work—site mix and ready mix—reviewed on ground floor beams and slabs. This study analyzes cost, quality, time, break-even points, and cash flow planning for both methods. The site mix method requires a cost of IDR 786,789,488.46 with a duration of 98.08 days, while the ready mix method is more economical at IDR 747,836,152.01 and faster at 95.79 days. In terms of quality, ready mix concrete performs better than site mix. The break-even point for cost occurs at a volume of 9.23 m³ with a cost of IDR 9,930,284.94, while the time break-even point is at 2.04 m³ within 0.43 hours. Cash flow analysis indicates a profit of IDR 166,618,719.86, equivalent to 16.72% of the contract value.